Homemade yeast by using tropical fruits through fermentation process - Che Kamaruddin, Aminul Hakim; Sani, Husna Izzati; Zolkifli, Nur Athirah; Abdul Rahman, Misbahul Muneer (Penerbit UTHM, 2020)
Yeast is one type of bacteria that is used in baking industry and as the crucial parameters to determine the softness of the bread. Many tropical fruits can be used as a medium to produce yeast. The main goal of this study is to produce homemade yeast by different types of fruits. The methods used to produce yeast are fermentation and separation process, where tropical fruits such as the banana, pineapple and raisin were used. The fruits are fermented for seven days, and they are supplied daily with calculated amount of sugar and flour. The yeast produced are then used in making apam, where three parameters are measured which are the volume of apam, the flavour and the aroma of apam. The best tropical fruits to produce yeast, arranged in order are raisin, banana and pineapple. We are unable to study further on the starfruit because it is seasonally unavailable during the research period. The result of the present study would provide knowledge and information about tropical fruits as homemade yeast. Additionally, this study will produce significant and relevant information for future studies regarding to homemade yeast.